Legal Protection of the Consumer in Electronic Commerce in Nigeria - Akomolede, Timothy Ifedayo (2015)
The study analysed the legal issues and problems involved in electronic commerce in Nigeria, examined the laws and institutions that protect consumers and assessed the remedies available to the latter. It also examined the prospects and challenges of a comprehensive consumer protection code for electronic commerce with a view to appraising the legal protection available to consumers in electronic commerce in Nigeria.